El Clima Organizacional Y Su Incidencia En El Desempeño Laboral Del Talento Humano De La Escuela De Conducción Para Choferes Profesionales “Manuel Bhrunnis Villacrés” De La Ciudad De Babahoyo. - MERCHÁN JÁCOME, VERÓNICA (2014)
This research entitled "The organizational climate and its impact on work performance of human talent Driving School for Professional Drivers" Manuel Bhrunnis Villacrés "Babahoyo City", aims to know in detail the management that develops this-union educational organization seeking that human talent providing a quality service to students and prospective members of this union organization. The paper is supported by classical and modern management concepts to determine the management model that is currently being implemented and reach conclusions and propose solutions to the problems identified, for the sole purpose of improving customer service. This paper presents criteria for teachers and students which are treated statistically and graphically presented for an understanding of the user of this academic report.